Sexual continence in the late nineteenth-century aesthetic tradition: Walter Pater, Lionel Johnson, Vernon Lee, George Moore - Green, S (2017)
This thesis contends that the idea of productive sexual continence – that is, abstinence from sexual activity understood as a constructive practice – significantly shaped a branch of thought within and around the British Aesthetic Movement of the late nineteenth century. Recent critical work has stressed sexual liberation or permissiveness as among the values of Aestheticism, and has read Aesthetic representations of continent states as indications of repressed, sublimated, or coded sexuality. Reading these representations through period-specific sexual discourses, I reveal an alternative discursive tradition within Aestheticism, in which the idea of productive sexual continence formed an important part of thinking about the 'aesthetic life', or the life lived according to aesthetic principles. The enquiry privileges the place of sexual ideas and values in the context of the intellectual culture of the Aesthetic Movement, and of the late-Victorian period generally, rather than focusing (as much scholarship has done) upon the writers' 'real-life' sexual behaviour, desires or identities. Sexual continence was often understood in the period as conducive both to individual health and happiness, and to one’s relationship with society. At a time when Aesthetic writers were often accused of endorsing excessive individualism and excessive sensuality, this idea facilitated the elaboration of an aesthetic ethic that could incorporate intense sensuous (but not sensual) pleasure and also responsible sociability. After an Introduction that outlines the scope and method of the thesis, Chapter One illustrates the ubiquity of this idea in medical writing (professional and popular) about the sexual body in the period, and within Classical and Christian intellectual discourses commonly drawn upon by Aesthetic authors. Four chapters follow in which roughly the same idea is shown to take a central role in representations of the 'aesthetic life' in the work of four major writers. Chapter Two posits that there were broadly two traditions of reading Walter Pater in the late nineteenth century: one in which he was taken as an apologist for a radical sensual individualism, and another that emphasized his advocacy of restraint and reserve as both stylistic and ethical principles. Informed by early readings in this latter tradition, I demonstrate the plausibility of an interpretation of Pater as carefully distinguishing between aesthetic sensuousness and sensuality. Pater also, I argue, can viably be read as assessing the ideal aesthetic life in terms of health and love, and representing sexual continence as compatible with both. Chapter Three looks at Lionel Johnson’s incorporation of this continent ideal into his Christianized cultural humanism, evolved in his letters, poetry, and criticism. In the poetry resistance to temptation is described as a process by which potentially sensual experience is made safely sensuous, while in the letters and criticism can be found admiration for various continent states that reconcile individual aesthetic experience with social responsibility. In Chapter Four, the pre-1900 essays of Vernon Lee are shown to be consistently anti-sensual, while distinguishing this sensuality from a kind of continent sense experience identified as aesthetic, and associated with Pater. Lee also uses this aesthetic sensuousness as a model for ideal – i.e. disinterested and respectful – relations between people, and between people and things. Chapter Five examines the co-existence of this discourse with other, contradictory models of aesthetic living in the work of George Moore. Moore was generally pro-sensual, and considered ‘sex’ (in the abstract) to be integral to art; but he also associated the production of art with continent states. An alternative, sexually continent Paterian tradition can, I argue, help to account for these discordant moments. A Conclusion briefly indicates the further relevance of such thinking beyond the bounds of the Aesthetic Movement.